(untitled) (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2026)
The phenomenon of Javenglish, characterized by the influence of Javanese accent and phonological features on English speech, has become increasingly prominent in Indonesian EFL classrooms, particularly among undergraduate students in English education programs. In many pedagogical contexts, a Javanese-accented variety of English is often framed as a deficiency or deviation from standard pronunciation norms. However, for learners, this variety may also serve as an expression of linguistic identity and cultural belonging. This study examines how Javanese-accented English is produced, perceived, and evaluated in EFL classroom interactions, focusing on the tension between institutional expectations of “standard” English pronunciation and students’ identity construction as Javanese speakers. Employing a qualitative approach, the research draws on classroom observations, audio-recorded oral performances, and semi-structured interviews with undergraduate EFL students and lecturers in Indonesian higher education settings. The analysis is informed by sociolinguistic and critical applied linguistics perspectives, particularly theories of accent, language ideology, and linguistic identity. The findings revealed that Javanese-accented English functioned not merely as a linguistic barrier but as a form of cultural pride and identity expression among undergraduate EFL learners, supporting learner confidence, classroom participation, and peer solidarity. Nevertheless, dominant ideologies privileging native-like pronunciation tended to marginalize such practices, thereby reinforcing unequal power relations in EFL classrooms. This study contributed to discussions on accent diversity in EFL pedagogy and advocated for more inclusive approaches that recognized local accents as legitimate forms of English use.